Nilai Sosial dan Edukasi dalam Kumpulan Dongeng Suku Mbojo - Kasman (Samudra Publisher, 2023)
As a cultural product from an area, fairy tales have many values ​​in it. This study aims to analyze social values and education values ​​of contained in the folklore of the Mbojo tribe. The research method used in this research is the descriptive qualitative method. The research data was taken from the book